Latent ischemic heart disease in sea captains. - Mundal, R.; Erikssen, J.; Rodahl, Kåre (Scandinavian Journal of Work, Environment & Health, 1982)
For 110 apparently healthy Norwegian captains on ocean-going ships a near maximal bicycle exercise test revealed a pathological exercise electrocardiogram for 10.0%, while the corresponding results for a comparable group of Oslo men and a group of Norwegian sea pilots were 4.6 and 11.8%, respectively. The significant difference in prevalence between the captains and Oslo men could not be explained by differences in serum lipids, blood pressure, or a family history of coronary heart disease. The captains were taller and more physically fit than the Oslo men, but they were significantly heavier and had a more rapid age decline in physical performance capacity and a higher prevalence of heavy smokers. Ten of the 11 captains with a pathological exercise electrocardiogram were, or had been, heavy smokers (greater than or equal to 20 cigarettes/d). A high caloric intake in relation to caloric expenditure, heavy smoking, and poorly defined factors such as stress, irregular workhours, and varying climatic conditions are factors to be considered as explanations for these findings. The claim by captains that they have a higher risk than average for developing coronary heart disease was to some extent corroborated in the present study.